Global Mobile Robot Path Planning using Laser Simulator - Ali, Mohammed A. H.; Wan Azhar, Wan Yusoff; Zamzuri, Hamedon; Zulkifli, Md. Yusof; Musa, Mailah (IEEE, 2017)
This paper presents the utilization of novel laser simulator search graph approach for global path determination in unknown environment using MATLAB. The environment of the robot is represented in 2D map and the laser simulator is used to find the collision free path within this environment without prior knowledge about the visiting cells. By using the laser simulator row points procedures, the point that determine the planned path in front of robot can be generated continuously and this process is repeated until the robot reaches the goal position. Two kinds of environments are used to test laser simulator; the first one is represented with cleared borders and polygons whereas the other includes some noises and uncertainties. The developed laser simulator is implemented successfully in these environments and the simulation results are compared with the classical A* algorithm. From the results, the laser simulator has advantages in computational time and low collision possibility in comparison with A* algorithm while the path cost of laser simulator is always greater than path cost of A* algorithm.